RELIGIOUS UNDERSTANDING OF ONLINE GAMBLING APPLICATION USERS AMONG MUSLIMS (CASE STUDY IN DOLOK MASIHUL SUBDISTRICT) - Arifa, Dwi Maulia; Harahap, Salahuddin (LPPM Univ. Ibn Khaldun Bogor, 2025)
The increasing phenomenon of online gambling among Muslims, particularly in Dolok Masihul District, has become a serious issue that reflects a significant gap between religious understanding and actual societal behavior. This study aims to examine the various forms of online gambling that are currently developing, the factors influencing Muslim involvement, and how religious understanding impacts gambling behavior. This research employs both sociological and Islamic theological approaches, using a qualitative descriptive method with data collected through interviews, observation, and documentation. The findings indicate that although most participants are aware that gambling is prohibited in Islam, this awareness alone is not sufficient to discourage them from continuing the practice. Economic pressures, social environment, misperceptions about personal skill, and the lack of religious guidance are the primary driving factors behind their involvement. Religious understanding that remains shallow and textual has not yet functioned as an effective moral compass. Therefore, a holistic approach that addresses theological, social, and educational aspects is urgently needed to address this issue.